(untitled) (World Bulletin of Social Sciences, 2023)
In this article, the scientific and theoretical foundations of communication functions in the socialization of students, the essence of communication functions in the socialization of students, the communication functions in the socialization process of students as a pedagogical problem, and the current state of communication functions in the socialization process of students are studied